Merdeka Belajar dalam Perspektif Ki Hajar Dewantara - Rini Budiwati; Endang Fauziati (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
As we know, Merdeka Learning is a program created by the Minister of Education, Culture, Research and Technology, Nadiem Makarim, which aims to make learning more enjoyable. This can be implemented in teacher and student innovation in the form of teacher innovation in delivering material accompanied by student innovation and creativity in learning. Taman Siswa as an educational place that was founded on the initiative of Ki Hajar Dewantara has principles that are in accordance with independent learning. These principles are: the individual's right to self-determination, independent learners, community members must be enlightened by education, education must be comprehensive, and the struggle for independence which is synonymous with free learning. Ki Hajar Dewantara's idea is that education is essentially the basis and effort to develop and advance culture, which is based on the values, rules or norms of mysticism and culture that exist in the community. Where culture belongs to every generation. Caring for independence in education can be started from how to develop independence starting from the classroom, education that emphasizes creativity, taste and initiative. Children as students in schools are human figures who are entitled to guidance, because they have their own nature, therefore, as educators, we have a duty to guide them to achieve their life goals. This is the security and happiness they want as members of a human being or society. stract describes in general the issue of the research reported in the manuscript.